Emergence of psycho-cognitive and socio-political perspectives during the dashboard appropriation process: The case of industrial SMEs in Morocco - Wissal, Haoudi; Mohammed, Kaoukabi; Mahouat, Nacer; Souad, Habbani (Edelweiss Applied Science and Technology, 2024)
The study aims to explore how the dashboard, initially designed to provide a rational view of organizational complexity, is appropriated by organizational actors in Moroccan Small and Medium Enterprises (SMEs). The process of appropriation is iterative and complex, involving modifications to the artifact dimension of the tool and adaptations by user-actors in their cognitive, behavioral, and social dynamics. The research highlights the psycho-cognitive and socio-political factors influencing the use of the dashboard as a key management control tool. The motivation behind this study is to understand why such a tool can lead to disruptions, resistance to change, contextualization issues, and adoption problems within organizations, rather than fulfilling its initial purpose of rationalizing processes and standardizing behaviors. The research adopts a qualitative approach using the case study method, specifically multiple embedded case studies. The sample consists of three Moroccan SMEs within the industrial food sector. We deemed it appropriate to use a textual data analysis approach, selecting two methods for this purpose: lexical analysis and thematic analysis. The qualitative data analysis was conducted using NVivo 12 software. The findings indicate that the Pre-Appropriation phase creates a context that balances technical and political factors to reduce resistance among stakeholders. The subsequent Original Appropriation Phase involves a collective decision to adopt the dashboard, which can lead to either compliant integration or deviations that enhance user adaptation. Lastly, the Reappropriation phase challenges established routines, potentially resulting in either meaningful transformations or superficial engagement with the dashboard's features. This study demonstrates that the iterative process of dashboard appropriation in Moroccan SMEs, influenced by psychocognitive and sociopolitical factors, can result in resistance, adoption challenges, and unanticipated organizational adaptations and transformations.